Geriatric rehabilitation as prevention of the syndrome of falls in diseases of the vessels of the lower extremities - K, Prashchayeu; N, Kolyago; D, Krylov; Y, Manerov (Magyar Gerontológia, 2023)
The aim To develop and to implement in clinical practice a program of geriatric rehabilitation as a prevention of the syndrome of falls in diseases of the vessels of the lower extremities.